SALIENT AREA DISCERNMENT VIA HIGH DIMENSIONAL COLOR TRANSFORM AND LOCAL SPECIAL PLATFORM - P. Santhiya; S. Selvi (International Journal of Engineering Technologies and Management Research, 2018)
Detecting visually salient regions in images is fundamental problems and it is useful for applications like image segmentation, adaptive compression, and object recognition. A salient object region is a soft decomposition of foreground and background image elements. To detect salient regions in an image in terms of the saliency maps. To create a saliency map by using a linear combination of colors in high-dimensional color space. To improve the performance of saliency estimation, utilize the relative location and color contrast between superpixels. To resolve the saliency estimation from trimap by using learning based algorithm. This is based on an examination that salient regions frequently have individual colors’ compared with backgrounds in human sensitivity however, human perception is complicated and extremely nonlinear. The tentative outcome on three benchmark datasets show that our approach is valuable in assessment with the prior state-of-the-art saliency estimation methods. Finally, salient region detection that outputs full resolution saliency map with well-defined boundaries of the salient object.